If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -4 + y + 24 = 8y + 20 + -6y Reorder the terms: -4 + 24 + 3y + y = 8y + 20 + -6y Combine like terms: -4 + 24 = 20 20 + 3y + y = 8y + 20 + -6y Combine like terms: 3y + y = 4y 20 + 4y = 8y + 20 + -6y Reorder the terms: 20 + 4y = 20 + 8y + -6y Combine like terms: 8y + -6y = 2y 20 + 4y = 20 + 2y Add '-20' to each side of the equation. 20 + -20 + 4y = 20 + -20 + 2y Combine like terms: 20 + -20 = 0 0 + 4y = 20 + -20 + 2y 4y = 20 + -20 + 2y Combine like terms: 20 + -20 = 0 4y = 0 + 2y 4y = 2y Solving 4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = 2y + -2y Combine like terms: 4y + -2y = 2y 2y = 2y + -2y Combine like terms: 2y + -2y = 0 2y = 0 Divide each side by '2'. y = 0 Simplifying y = 0
| 4(2p+7)-5(p-1)=12 | | x+x+1=121 | | 9y(2+4)=5(5+2) | | 3/2(3x+5)=-24 | | 5x+22=(-4)+6 | | 21+16x+80=37x+17 | | .15x=40+.05x | | 17x+9=13x-15 | | 17x+7y=11 | | 3x^2-16xy+5y^2=0 | | -15+2x+x^2=0 | | 20r=5 | | 8x^2+23=0 | | -2(t-6)-(t+1)=6 | | 6(-5x+1)-3(4x-12)=3x-9-(3x-9) | | 3=-3(y+5) | | 3=-39y | | x^2-21x-110=0 | | (-7)+9+(-6)= | | 3c-2c=5 | | v+(v-30.4)+(v+25.7)=191.5 | | q=3n+3u | | 2a-16+3a+2=6(a+3) | | 8x-7=5x+6 | | x(x-3)=x(2x-5) | | 2+3x-2x^2=0 | | 4x-12y+4= | | 15y+45=2y+6 | | 2(x-8)=16 | | 7e^2+4e-3-e^2= | | 119=-7r | | -(7y+3)-(-6y-7)=2 |